International Home Dialysis Consortium: declaration advocating for the promotion of home dialysis globally - Brown, Edwina A.; Jha, Vivekanand; Bavanandan, Sunita; Chan, Christopher T.; Davies, Simon; Figueirido, Ana; Liew, Adrian; Madero, Magdalena; Niang, Abdou; Mehrotra, Rajnish; Mitra, Sandip; Rutherford, Peter; et al. (Kidney international. Reports, 2025)
The use of home dialysis (peritoneal dialysis [PD] and home hemodialysis [HHD]) is variable in high-income countries despite its known lifestyle benefits and lower costs, and is unavailable or underused in many lower-income countries, where PD could increase access to dialysis. The International Home Dialysis Consortium (IHDC) is a joint project of the ISN and the International Society for Peritoneal Dialysis (ISPD). The consortium has been established to address the challenges and barriers to and improve the adoption of home dialysis globally. A launch meeting was held at the World Congress of Nephrology 2024 in Buenos Aires, Argentina, focusing on 4 areas - empowering people needing dialysis, nephrology workforce education, developing workforce and resources, and integrating care and payment policies. The key statements from each group were then amalgamated to produce a manifesto that advocates for the global promotion of home dialysis (PD and HHD) to enhance patient experience, quality, and equity in kidney failure care. This manifesto will be presented to professional kidney-related societies (medical, nursing, patients, and technical) to adopt the declaration as a practical roadmap to increase home dialysis awareness and, consequently, modality selection.
Online verfügbar: 14. März 2025, Artikelversion: 5. Juni 2025
Gesehen am 19.01.2026